Haploidentical Stem Cell Transplantation With a Novel Conditioning Regimen in Older Patients: A Prospective Single-Arm Phase 2 Study - Sun, Yu-Qian; Han, Ting-Ting; Wang, Yu; Yan, Chen-Hua; Wang, Feng-Rong; Wang, Zhi-Dong; Kong, Jun; Chen, Yu-Hong; Chen, Huan; Han, Wei; Chen, Yao; Zhang, Yuan-Yuan; et al. (Frontiers in Oncology, 2021)
Objective: Haploidentical stem cell transplantation (haplo-SCT) has demonstrated encouraging results in younger patients. There is also an increasing need for haplo-SCT in older patients. However, the high risk of treatment-related mortality (TRM) in older patients is still a major concern. We aimed to investigate a novel conditioning regimen (Bu/Flu/Cy/ATG) followed by haplo-SCT in older patients. Method: This prospective, single-arm clinical trial was performed at Peking University Institute of Hematology, China. Patients were enrolled if they were (1) diagnosed with acute leukemia or MDS; (2) without MSD and MUD, and with HID available; and (3) age ≥55 years. The Bu/Flu/Cy/ATG regimen consisted of the following agents: Ara-C (2 g/m2/day, injected i.v.) on days-10 and−9; BU (9.6 mg/kg, injected i.v. in 12 doses) on days-8,−7, and−6; Flu (30 mg/m2/day, injected i.v.) from day−6 to day−2; Cy (1 g/m2/day, injected i.v.) on days−5 and−4; semustine (250 mg/m2, orally) on day-3 and antithymocyte globulin (ATG) [2.5 mg/kg/day, rabbit, SangStat (Lyon, France)] on days−5,−4,−3, and−2. The primary endpoint was 1-year TRM. Results: From April 1, 2018 to April 10, 2020, a total of 50 patients were enrolled. All patients achieved neutrophil engraftment with complete donor chimerism. The cumulative incidence of grade 2-4 aGVHD at day-100 was 22.0%. The cumulative incidences of CMV viremia and EBV viremia on day 100 were 68.0 and 20.0%, respectively. The cumulative incidence of TRM at 1-year was 23.3%. and the cumulative incidence of relapse (CIR) at 1 year after transplantation was 16.5%. The overall survival (OS) and leukemia-free survival (LFS) at 1 year were 63.5 and 60.2%, respectively. The outcomes were also comparable with patients who received Bu/Cy/ATG regimen using a propensity score matching method. Conclusions: In conclusion, this study suggested that a novel conditioning regimen followed by haploidentical HSCT might be a promising option for older patients. The study was registered as a clinical trial. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT03412409.